2016
DOI: 10.1097/j.pain.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a mouse model of headache

Abstract: Migraine and other primary headache disorders affect a large population and cause debilitating pain. Establishing animal models that display behavioral correlates of long-lasting and ongoing headache, the most common and disabling symptom of migraine, is vital for the elucidation of disease mechanisms as well as the identification of drug targets. We have developed a mouse model of headache, using dural application of capsaicin along with a mixture of inflammatory mediators (IScap) to simulate the induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…The primary goal of this study was to measure whether commonly used inflammatory agents that have been applied to the cranial dura of rats and lately also in mice (30), namely 5-HT and PGE 2 , can pass through the dura and reach detectable levels in the CSF and CNS. In addition, we have attempted to estimate by extrapolation from these measurements the CSF and CNS levels that would be attained in behavioral studies that use dural application of higher concentrations and quantities of these inflammatory mediators as a headache-inducing stimulus, and to evaluate whether these estimated central levels would be expected to have behavioral or physiological effects, based on previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary goal of this study was to measure whether commonly used inflammatory agents that have been applied to the cranial dura of rats and lately also in mice (30), namely 5-HT and PGE 2 , can pass through the dura and reach detectable levels in the CSF and CNS. In addition, we have attempted to estimate by extrapolation from these measurements the CSF and CNS levels that would be attained in behavioral studies that use dural application of higher concentrations and quantities of these inflammatory mediators as a headache-inducing stimulus, and to evaluate whether these estimated central levels would be expected to have behavioral or physiological effects, based on previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For future studies with such models it would be of interest to determine which of the observed behavioral changes can be evoked by the lower concentrations that have been shown to be effective for activating and sensitizing meningeal nociceptors (6, 9). In addition, the possibility of central effects will be increased in studies that use mouse instead of rat (30), due to a higher transdural permeability (27). …”
Section: Discussionmentioning
confidence: 99%
“…The sequence of COX-1 linked to TXAS through a 10-aa linker (COX-1-10aa-TXAS) was produced by PCR and subcloning procedures using similar methods as previously described. [19][20][21][22] Through the PCR cloning method, the cDNA was successfully subcloned into the pcDNA 3.1(+) vectors between the two BamHl sites containing a cytomegalovirus early promoter. The correct inserted size of cDNA was confirmed by restriction enzyme digestion analysis and DNA sequencing.…”
Section: Engineering Of the Schec Cox-1-10aa-txas Cdna And Subcloningmentioning
confidence: 99%
“…Here, we investigated whether endogenous TRESK activity regulates the generation of headache-related behaviors in mice (Huang et al, 2016). After recovery from craniectomy for 7 days, both WT and TRESK KO mice exhibited some spontaneous forepaw wiping and hindpaw We went on to ask whether loss of TRESK alters the likelihood to manifest headacherelated behaviors in mice.…”
Section: Dural Afferent Neurons From Tresk Ko Mice Show Higher Intrinmentioning
confidence: 99%